Reduction of Concentrating Poisonous Metallic Radicals from Industrial Wastewater by Forward and Reverse Osmosis (Journal of Engineering, 2012)
The research aims to use a new technology for industrial water concentrating that contains poisonous metals and recovery quantities from pure water. Therefore, the technology investigated is the forward osmosis process (FO). It is a new process that use membranes available commercial and this process distinguishes by its low cost compared to other process. Sodium chloride (NaCl) was used as draw solution to extract water from poisonous metals solution. The driving force in the FO process is provided by a different in osmotic pressure (concentration) across the membrane between the draw and poisonous metals solution sides. Experimental work was divided into three parts. The first part includes operating the forward osmosis process using TFC membrane as flat sheet for NaCl. The operating parameters studied were: draw solutions concentration (10 – 95 g/l), draw solution flow rate (12-36 I/h), temperature of draw solution (30 and 40°C), feed solution concentration (10 -210 mg/l), feed solution flow rate (10 -50 l/h), temperature of feed solution (30 and 40°C) and Pressure (0.4 bar). The second part includes operating the forward osmosis process using CTA membrane as flat sheet for NaCl. The operating parameters studied were: draw solution concentration (15 – 95 g/l), feed solution concentration (10-210 mg/l). Constant temperature was maintained at 30°C. The last part includes operating the reverse osmosis process using TFC membrane as spiral wound module in order to separate NaCl salt from draw solution and obtain on pure water so as to usefully in different uses and also obtain on solution of NaCl concentrate which was recirculated to forward osmosis process. It is then used as draw solution. The operating parameter studied was: feed solution flow rate (15-55 l/h). The experimental results show that the water flux increases with increasing draw solution concentration, feed solution flow rate, temperature of draw solution and decreases with increasing feed solution concentration, draw solution flow rate and temperature of feed solution. The experiments also show that CTA membrane gives higher water flux than TFC membrane for forward osmosis operation.